Low-viscosity AB type gel flame retardant for preventing and treating wildfire
Through the combination of low viscosity agent A and agent B, a high viscosity gel flame retardant is formed, which solves the problems of low viscosity of traditional fire extinguishing agents and poor fluidity of gel flame retardant, and achieves efficient flame retardant and smoke suppression effects, which are suitable for modern fire extinguishing methods.
Patent Information
- Application Number
- CN202510691974.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-08-12
AI Technical Summary
The existing water-based fire extinguishing agent has low viscosity and poor water retention, large viscosity of gel flame retardant, insufficient smoke suppression performance and poor fluidity, which limits its application in modern fire extinguishing methods.
A type of gel flame retardant composed of low viscosity A agent and B agent. A agent consists of gelatin, chaotropic salt and antibacterial agent. A agent consists of negatively charged silica sol and modified black phosphorus nanosheets. By mixing, it can improve its dispersion and fluidity in the substrate.
It achieves efficient and environmentally friendly flame retardant performance, significantly reduces the peak heat release rate and flue gas release rate, improves the limit oxygen index, and enhances the adhesion and thermal insulation effect on the surface of solid combustible materials.
Smart Images

Figure BDA0005422137800000051 
Figure BDA0005422137800000052 
Figure HDA0005422137810000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flame retardancy, and in particular to a low-viscosity AB type gel flame retardant for wildfire prevention and control. Background Art
[0002] As one of the most frequent and difficult-to-handle major natural disasters worldwide, forest fires are becoming increasingly prevalent. In recent years, with global warming and the frequent occurrence of extreme weather events, forest fires have reached a peak. According to statistics, in 2023 alone, over one million hectares of land were affected by fires worldwide, with fires at the forest-urban interface being the most devastating. For example, the February 2023 Guizhou forest fires, which quickly ignited over 200 fire points and affected hundreds of towns, not only severely damaged the ecosystem but also directly threatened the lives and property of the people, generating widespread social impact.
[0003] In the field of forest fire prevention and control technology, the application of flame retardants and fire extinguishing agents is an important means to reduce the incidence and severity of fires. Currently, the mainstream wildfire prevention and control fire extinguishing agents on the market mainly include water-based fire extinguishing agents and foam fire extinguishing agents. However, these traditional fire extinguishing agents have obvious technical defects: on the one hand, their low viscosity and easy spraying properties are conducive to rapid application, but their water retention is poor, and it is difficult to provide long-term flame retardant protection under the influence of environmental wind and sunlight; on the other hand, common hydrogel flame retardants (such as gels prepared based on guar gum, xanthan gum, and silica) have good flame retardant effects, but their performance is limited by environmental humidity. Once the water evaporates, the flame retardant function is lost. In addition, the high viscosity of traditional hydrogels not only limits their fluidity in pipes, but also makes them unsuitable for modern fire extinguishing methods such as drone spraying. Their large yield stress also affects the material's wetting properties on the surface of solid combustible materials. Summary of the Invention
[0004] To address the shortcomings of traditional water-based fire extinguishing agents, such as low viscosity and poor water retention, as well as the high viscosity, insufficient smoke suppression, and poor fluidity of existing gel flame retardants, this invention proposes a low-viscosity AB-type gel flame retardant for wildfire prevention and control. The technical problem to be solved is how to improve the viscosity of the gel flame retardant so that it can be evenly dispersed or penetrated into the substrate through methods such as spraying, avoiding the uneven coating and microstructure clogging caused by traditional high-viscosity flame retardants. This innovative technology is expected to provide a more efficient and environmentally friendly solution for forest fire prevention and control.
[0005] The present invention solves the above technical problems through the following technical methods:
[0006] A low-viscosity AB type gel flame retardant for wildfire prevention and control comprises a low-viscosity A agent and a low-viscosity B agent.
[0007] The raw materials of the low-viscosity agent A are composed of 5-20% gelatin, 5-25% chaotropic salt, 0.1-1% antibacterial agent, and the balance water.
[0008] The raw materials of the low-viscosity agent B are composed of 5-55% of negatively charged silica sol, 1-5% of modified black phosphorus nanosheets, and the balance of water in terms of mass percentage.
[0009] Preferably, the chaotropic salt is a mixture of one or more of sodium iodide, sodium chloride, sodium nitrate and sodium hexafluorophosphate.
[0010] Preferably, the antibacterial agent is one of potassium sorbate and sodium diacetate or a mixture of the two.
[0011] Preferably, the negatively charged silica sol is TM-50 and AS-40 from Sigma, preferably TM-50.
[0012] Preferably, the modified black phosphorus nanosheets are prepared by a solvothermal reaction using black phosphorus nanosheets, copper salt and sodium acetate as raw materials and an organic solvent as a solvent. The mass ratio of the black phosphorus nanosheets and the copper salt is 3:1-9, and the mass ratio of the sodium acetate and the copper salt is 4:1. Further preferably, the copper salt is copper acetate, the organic solvent is ethylene glycol, the temperature of the solvothermal reaction is 190-230°C, and the reaction time is 1.5 hours. The specific preparation method may be: mixing black phosphorus nanosheets, copper acetate and sodium acetate in ethylene glycol. The mixture is sealed in an autoclave and reacted at 190-230°C for 1.5 hours. The product is then collected by centrifugation, washed with ethanol, and vacuum dried to obtain the modified black phosphorus nanosheets.
[0013] Preferably, the water is deionized water or industrial soft water.
[0014] The gel flame retardant provided by the present invention includes a low-viscosity agent A and a low-viscosity agent B. When preparing the gel, the mass ratio of low-viscosity agent A to low-viscosity agent B is preferably 1:1-2. Agents A and B are both low-viscosity liquids. After mixing, the two form a hydrogel within 1 hour.
[0015] The low-viscosity agent A provided by the present invention comprises 5-25%, preferably 10-15%, and more preferably 10% or 15% of a chaotropic salt. The chaotropic salt is a water structure disruptor that can regulate the structure of gelatin protein, disrupt the hydrogen bond network of water molecules, increase its disorder, weaken the triple helix structure of gelatin, and significantly reduce the viscosity of the agent A.
[0016] The low-viscosity agent A provided by the present invention comprises 5-20% gelatin, preferably 10-15%, and more preferably 10% or 15%. The gelatin enhances the adhesion of the hydrogel to the surface of solid combustible materials. The low surface tension of gelatin facilitates the wetting of the hydrogel. In addition, the negatively charged silica sol in agent B can adsorb the chaotropic salt in agent A, releasing the triple helical structure of gelatin and promoting the formation of a highly viscoelastic hydrogel.
[0017] The low-viscosity agent B provided by the present invention comprises 1-5%, preferably 5%, of modified black phosphorus nanosheets, which can catalyze the formation of gelatin carbon layers in agent A and catalyze the oxidation of carbon monoxide to reduce fire smoke concentration.
[0018] The low-viscosity agent B provided by the present invention comprises 5-55%, preferably 50%, of negatively charged silica sol. The silica sol can form a heat-insulating aerogel on the surface of solid combustible materials at high temperatures, preventing the spread of flames. Furthermore, the silica sol in agent B can interact with the chaotropic salt in agent A, reducing the concentration of salt ions that interact with gelatin. Therefore, mixing agents A and B can induce the rapid formation of a triple helical structure in gelatin. Once the triple helical structure is established, the system becomes more viscous and takes on a gel-like state.
[0019] The gel flame retardant provided by the present invention comprises 0.1-1%, preferably 0.1%, of an antibacterial agent, which functions to prevent microbial corrosion of protein, and is preferably potassium sorbate.
[0020] The present invention also provides a method for preparing the low-viscosity AB-type gel flame retardant, comprising the following steps: sequentially adding gelatin, a chaotropic salt, and an antibacterial agent to water, heating and stirring to form a low-viscosity Agent A; and sequentially adding a negatively charged silica sol and modified black phosphorus nanosheets to water, stirring at room temperature to form a low-viscosity Agent B. Both Agents A and B are low-viscosity systems capable of flowing within a pipe. When used on-site, Agents A and B are mixed in a predetermined ratio to form a gel within one hour.
[0021] The present invention further proposes the use of the low-viscosity AB type gel flame retardant in wood flame retardant treatment.
[0022] Preferably, during the specific application process, the low-viscosity agent A and agent B are mixed with a stirrer at a weight ratio of 1:1-2, and then applied to the wood surface using a spray gun. The fireproof gel can be formed after the wood is dried at room temperature for 1 hour.
[0023] The beneficial effects of the present invention are embodied in:
[0024] This invention innovatively utilizes the disruptive effect of chaotropic salts on the triple helix structure of gelatin to prepare a low-viscosity agent A. The silica in agent B selectively adsorbs the chaotropic salt in agent A, releasing the triple helix structure of gelatin in agent A. This results in a high-viscosity gel formed upon mixing the low-viscosity agents A and B. The modified black phosphorus nanosheets in the gel flame retardant exhibit excellent CO catalytic activity and selectivity, suppressing smoke release. Furthermore, at high temperatures, black phosphorus catalyzes gelatin to form a flame-retardant, heat-insulating carbon layer, protecting the substrate from flames. At high temperatures, silica sol can in situ form silica aerogel, providing thermal insulation. The interaction of the components in the aforementioned proportions results in the AB-type gel flame retardant exhibiting excellent flame retardancy. Experimental results show that the yield stresses of both agents A and B are less than 1 Pa, and a 1:2 mixture of the two achieves a yield stress of 2000 Pa. The limiting oxygen index of the wood board modified with the hydrogel increases from 21.6% to 39.2%, and the peak heat release rate increases from 512 kW / m². 2 Down to 121kW / m 2 ; Peak smoke release rate from 1.21m 2 / s dropped to 0.09m 2 / s. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the EDS-mapping diagram of the modified black phosphorus nanosheets synthesized in Example 1 of the present invention.
[0026] Figure 2 This is the XRD pattern of the modified black phosphorus nanosheets synthesized in Example 1 of the present invention.
[0027] Figure 3 This is a schematic diagram of the present invention using a butane torch flame to act on the hydrogel synthesized in Example 1.
[0028] Figure 4 The morphology of the expanded carbonized layer of the hydrogel synthesized in Example 1 of the present invention at different times under the action of a butane torch flame is shown in the figure, with pure water used as a comparison.
[0029] Figure 5 The viscosity of the hydrogels synthesized in Example 1 of the present invention and Comparative Examples 1-7 varies with shear rate.
[0030] Figure 6 The oscillation stress of the hydrogels synthesized in Example 1 of the present invention and Comparative Examples 1-7 varies with the oscillation strain.
[0031] Figure 7 Comparison of the yield stress of hydrogels with different AB agent mass ratios synthesized in Example 1 of the present invention and Comparative Examples 1-7.
[0032] Figure 81 is a morphology comparison diagram of the hydrogels with different AB agent mass ratios synthesized in Example 1 of the present invention and Comparative Examples 1-7.
[0033] Figures 5-7 in Ge 15 I 15 Represents Agent A with gelatin and sodium iodide concentrations of 15%, CSP 50 Represents the B agent with a silica sol concentration of 50%, Ge 15 I 15 :CSP 50 Represents the mass ratio of agent A to agent B. DETAILED DESCRIPTION
[0034] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the embodiments described are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.
[0035] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0036] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions.
[0037] Example 1
[0038] A method for preparing a low-viscosity AB type gel flame retardant comprises the following steps:
[0039] (1) Synthesis of modified black phosphorus nanosheets
[0040] 2g of black phosphorus nanosheets were mixed with 5g of copper acetate and 20g of sodium acetate in 2500g of ethylene glycol. The mixture was then sealed in a high-pressure reactor and reacted at 210°C for 1.5 hours. The mixture was then separated by centrifugation at 8000 rpm for 5 minutes. The resulting product was washed with ethanol and dried in a vacuum oven at 80°C for 12 hours to obtain black phosphorus nanosheets and copper oxide powder, which are modified black phosphorus nanosheets. Figure 1 It can be observed that oxygen and copper elements are evenly distributed on the surface of phosphorus, which indicates the successful loading of copper oxide. Figure 2 Only phosphorus peaks are observed in the XRD pattern, demonstrating that copper oxide is amorphously supported on black phosphorus. The two-dimensional black phosphorus in the image is composed of black phosphorus nanosheets only a few nanometers thick, which exhibit good dispersion. The BulkBP in the image is composed of large, layered black phosphorus crystals that are difficult to disperse in solution and will precipitate.
[0041] (2) Preparation of low viscosity agent A
[0042] The raw materials include the following components in terms of mass percentage: 15% gelatin, 15% chaotropic salt - sodium iodide, 0.1% antibacterial agent potassium sorbate, and the balance is water; gelatin, potassium sorbate and sodium iodide are added to water and stirred at 55° C. for 1 hour to form a low-viscosity agent A.
[0043] (3) Preparation of low viscosity agent B
[0044] The raw materials include the following components in percentage by mass: 50% TM-50 silica sol, 5% modified black phosphorus nanosheets, and the balance water; the silica sol and modified black phosphorus nanosheets are added to water and stirred at room temperature to form a low-viscosity B agent.
[0045] (4) Preparation of low viscosity AB type gel flame retardant
[0046] When used for fire extinguishing or as a flame retardant, mix agent A and agent B in a weight percentage of 1:2 to form a high-viscosity, high-elasticity gel flame retardant.
[0047] Example 2
[0048] A method for preparing a low-viscosity AB type gel flame retardant is different from Example 1 only in that the mass percentage of gelatin in Agent A is 5%.
[0049] Comparative Examples 1-7
[0050] A method for preparing a low-viscosity AB type gel flame retardant is different from Example 1 only in that the mixing ratio of agent A and agent B is different. The specific ratio is shown in Table 2.
[0051] The prepared hydrogel was used for flame retardant surface treatment of wood. The hydrogel was coated on the wood surface, dried at room temperature, and then baked with a butane gun (1200°C). Figure 3 The results are shown in the following table: Figure 4 As shown, the limiting oxygen index and heat release rate were tested according to international standards ISO 4589-22017 and ISO 5660. The CO release rate and smoke release rate were tested using a cone calorimeter (ISO 5660-1:2015). The specific test results are shown in Tables 1 and 2 below.
[0052] Table 1. Test results of the flame retardant effect of the gel flame retardant prepared in Example 1 and Example 2 on wood
[0053]
[0054] Table 2. Test results of wood flame retardancy of gel flame retardants prepared in Comparative Examples 1-7 of the present invention
[0055]
[0056]
[0057] As can be seen from the above, compared with the wood boards treated with pure water or the untreated wood boards (Table 1), the peak heat release rate, peak CO release rate and peak smoke release rate of the wood boards treated with the material in Example 1 were significantly reduced, and the limiting oxygen index was significantly improved. Figure 4 As shown, qualitative studies have shown that under the action of butane flame, the hydrogel coating can spontaneously expand to form a heat-insulating carbon layer, which prevents the combustion of the wooden board in the hydrogel protection area, which proves the effective flame retardancy of the material in Example 1 against solid combustibles.
[0058] According to Table 2, it can be seen that changing the ratio of agent A and agent B has a greater impact on the flame retardant performance. Increasing the proportion of agent A will lead to an increase in the release of smoke and CO, while increasing the proportion of agent B will lead to a decrease in the limiting oxygen index and flame retardant performance. The flame retardant and smoke suppression properties are best when the ratio of agent A to agent B is 1:1 and 1:2.
[0059] In addition, the viscoelasticity of the hydrogel of the present invention was tested ( Figure 5-8 ). It can be seen that both Agent A (1:0) and Agent B (0:1) have low viscosities (<50mPa·s), and the viscosity increases significantly after the two are mixed (>900mPa·s). As for the yield stress, it can be seen that the yield stresses of Agent A (1:0) and Agent B (0:1) are 0 and 0.91Pa, respectively. After the two are mixed, the yield stress of the system increases significantly, reaching a maximum of 2058Pa. This proves the effectiveness of mixing low-viscosity Agent A and low-viscosity Agent B to form a highly viscoelastic hydrogel.
[0060] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A low-viscosity AB-type gel flame retardant for wildfire prevention, characterized by: Including low viscosity A agent and low viscosity B agent: The raw materials of the low-viscosity agent A are composed of 5-20% gelatin, 5-25% chaotropic salt, 0.1-1% antibacterial agent, and the balance water. The raw materials of the low-viscosity agent B are composed of 5-55% of negatively charged silica sol, 1-5% of modified black phosphorus nanosheets, and the balance of water in terms of mass percentage.
2. The low-viscosity AB type gel flame retardant for wildfire prevention according to claim 1, characterized in that: The chaotropic salt is a mixture of one or more of sodium iodide, sodium chloride, sodium nitrate and sodium hexafluorophosphate.
3. The low-viscosity AB type gel flame retardant for wildfire prevention according to claim 1, characterized in that: The antibacterial agent is one of potassium sorbate and sodium diacetate or a mixture of the two.
4. The low-viscosity AB type gel flame retardant for wildfire prevention according to claim 1, characterized in that: The negatively charged silica sols are TM-50 and AS-40 produced by Sigma.
5. The low-viscosity AB type gel flame retardant for wildfire prevention according to claim 1, characterized in that: The modified black phosphorus nanosheets are prepared by a solvothermal reaction using black phosphorus nanosheets, copper salt and sodium acetate as raw materials and an organic solvent as solvent. The mass ratio of the black phosphorus nanosheets to the copper salt is 3:1-9, and the mass ratio of the sodium acetate to the copper salt is 4:
1. The temperature of the solvothermal reaction is 190-230°C and the reaction time is 1.5 hours.
6. The low-viscosity AB type gel flame retardant for wildfire prevention according to claim 1, characterized in that: When preparing the gel, the low viscosity agent A and the low viscosity agent B are mixed in a mass ratio of 1:1 to 2.
7. A method for preparing the low-viscosity AB type gel flame retardant according to any one of claims 1 to 6, characterized in that: Gelatin, chaotropic salt and antibacterial agent are added to water in sequence, heated and stirred to form low-viscosity agent A; negatively charged silica sol and modified black phosphorus nanosheets are added to water in sequence, stirred at room temperature to form low-viscosity agent B; when used on site, low-viscosity agent A is mixed with low-viscosity agent B to form a gel within 1 hour.
8. Use of the low-viscosity AB type gel flame retardant according to any one of claims 1 to 6 in flame retardant treatment of wood.
9. The use according to claim 8, characterized in that: When used on site, low viscosity agent A and low viscosity agent B are mixed with a stirrer in a mass ratio of 1:1 to 2, and then applied to the wood surface with a spray gun. After the wood is dried at room temperature for 1 hour, a fire retardant gel is formed.